The Household Cash Flow Channel of Monetary Policy - La Cava, Gianni; La Cava, G (Reserve Bank of Australia, 2016)
We explore whether changes in interest rates affect household consumption by changing the amount of cash that households have to spend – the household cash flow channel of monetary policy. Based on a panel of Australian households, we find that, when interest rates decline, the cash flows and durable goods spending of households with variable-rate mortgage debt increases relative to comparable fixed-rate borrowers. This is consistent with a ‘borrower’ cash flow channel. We also find that lower interest rates reduce the cash flows available to households that receive interest on bank deposits and that this, in turn, is associated with lower spending by these households. This is consistent with a ‘lender’ cash flow channel. Overall, the borrower channel is a stronger channel of monetary transmission than the lender channel, such that lower interest rates will typically increase household cash flows and lead to higher spending in aggregate. The central estimates imply that lowering interest rates by 100 basis points would be associated with an increase in aggregate household expenditure of about 0.1 to 0.2 per cent per annum. Overall, the household cash flow channel appears to be an important channel of monetary transmission in Australia.
Research Discussion Papers
Keywords: Finance; Income, wealth and finances; Finance; Income, wealth and finance